Personalized Therapy in a Patient With EGFR-Mutated NSCLC Developing Sequential CCDC6-RET Fusion and BRAF V600E Mutation as Bypass Resistance Mechanisms - Arianna Marinello, MD; Claudia Parisi, MD; Damien Vasseur, PhD; David Combarel, PharmD; Juliette Bihoreau, NP; Pernelle Lavaud, MD; Rémy Ezzedine, MD; Lodovica Zullo, MD; Luc Friboulet, PhD; Gerard Zalcman, MD, PhD; Antoine Italiano, MD, PhD; Benjamin Besse, MD, PhD; et al. (JTO Clinical and Research Reports)
In this case report, we describe a case of sequential acquired CCDC6-RET fusion and BRAF V600E mutation observed in a patient with EGFR-mutated NSCLC treated with osimertinib and with combined selpercatinib and osimertinib. The discovery of genomic resistance mechanisms was facilitated by serial liquid and tissue biopsies and molecular tumor board discussion. After the identification of CCDC6-RET fusion, the patient received a combination of selpercatinib and osimertinib with prolonged benefit and manageable toxicity. When a novel BRAF V600E mutation was detected at progression, the molecular tumor board suggested the administration of triple therapy, adding trametinib (anti-MEK). Nevertheless, treatment was discontinued for toxicity, highlighting the challenges of using multiple drug combinations to address complex resistance.